Environmental drivers and interaction mechanisms of heavy metal and antibiotic resistome exposed to amoxicillin during aerobic composting - Liu, Ning; Li, Gang; Su, Ya; Zhao, Yi; Ma, Jun; Huang, Guangqun (Frontiers in Microbiology, 2023)
The environmental accumulation and spread of antibiotic resistance pose a major threat to global health. Aerobic composting has become an important hotspot of combined pollution (e.g., antibiotic resistance genes (ARGs) and heavy metals (HMs)) in the process of centralized treatment and resource utilization of manure. However, the interaction mechanisms and environmental drivers of HMs resistome (MRGs), antibiotic resistance (genotype and phenotype) and microbiome during aerobic composting under the widely used amoxicillin (AMX) selection pressure are still poorly understood. Here, we investigated the dynamics of HMs bioavailability and their MRGs, AMX-resistant bacteria (ARB) and antibiotic resistome (ARGs and intⅠ1), and bacterial community to decipher the impact mechanism of AMX by conducting aerobic composting experiments. We detected higher exchangeable HMs and MRGs in the AMX group than the control group, especially for the czrC gene, indicating that AMX exposure may inhibit HMs passivation and promote some MRGs. The presence of AMX significantly altered bacterial community composition and AMX- resistant and -sensitive bacterial structures, elevating antibiotic resistome and its potential transmission risks, in which the proportions of ARB and intⅠ1 were greatly increased to 148-fold and 11.6-fold compared to the control group. Proteobacteria and Actinobacteria were significant biomarkers of AMX exposure and may be critical in promoting bacterial resistance development. S0134_terrestrial_group was significantly negatively correlated with blaTEM and czrC genes, which might play a role in the elimination of some ARGs and MRGs. Except for the basic physicochemical (MC, C/N, pH) and nutritional indicators (NO3−-N, NH4+-N), Bio-Cu may be an important environmental driver regulating bacterial resistance during composting. These findings suggested the importance of the interaction mechanism of combined pollution and its synergistic treatment during aerobic composting need to be emphasized.